Berat Organ Non Karkas Ayam Broiler Setelah Disuplementasi Dl-Methionine dalam Pakan - Selviana Suni; Charles Venirius Lisnahan; Agustinus Agung Dethan (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2021)
The purpose of this research was to determine the effect of dl-methionine supplementation in feed on the non-carcass organ performance of broilers. The research was conducted at the Laboratory of Animal Husbandry Study Program, Agricultural Faculty, University of Timor, Kefamenanu from December 2019 to January 2020. The research used 80 fourteen-day broilers. The method used in this research was an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 4 replications. The treatments tested were: T0 (Control feed), T1 (T0 + 0.30% dl-methionine), T2 (T0 + 0.50% dl-methionine), and T3 (T0 + 0.70% dl-methionine). The variables observed were the percentage of non-carcass weight, percentage of blood, percentage of slaughter weight, percentage of the head weight, percentage of neck weight, and the percentage of abdominal fat. The results of the research showed that the treatment significantly affected the weight and percentage of blood, feathers, slaughter weight, and non-carcasses of broilers (P <0.05) while the weight and percentage of the head, neck, and abdominal fat had no significant effect. Average head weight of T0 : 48,58±2,29; T1: 46,07±2,83; T2: 48,48±8,35; and T3: 52,36±4,13 g/head. Neck weight T0: 66,10±11,74; T1: 69,53±4,60; T2: 70,67±19,01; and T3: 82,13±8,45 g/head. Weight of abdominal fat T0: 20,57±2,49; T1: 22,91±8,39; T2: 27,87±11,94; and T3: 26,62±9,56 g/head.. It was concluded that commercial feed supplemented with dl-methionine by 0.70% increased the growth and development of non carcass featherweight, blood weight, head and neck weight, abdominal fat, slaughter weight of broiler chickens.